A near-global, high resolution land surface parameter dataset for the variable infiltration capacity model - Jacob R. Schaperow (Nature Portfolio, 2021)
Measurement(s) vegetation characteristics • soil characteristics • elevation Technology Type(s) satellite imaging • soil sampling • digital curation Factor Type(s) geographic location Sample Characteristic - Environment vegetation layer • soil Sample Characteristic - Location global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14869500